The Rhinobiome of Exacerbated Wheezers and Asthmatics: Insights From a German Pediatric Exacerbation Network - Aydin, Malik; Weisser, Cornelius; Rué, Olivier; Mariadassou, Mahendra; Maaß, Sandra; Behrendt, Ann-Kathrin; Jaszczyszyn, Yan; Heilker, Tatje; Spaeth, Maximilian; Vogel, Silvia; Lutz, Sören; Ahmad-Nejad, Parviz; et al. (Frontiers in Allergy, 2021)
Although the nose, as a gateway for organism–environment interactions, may have a key role in asthmatic exacerbation, the rhinobiome of exacerbated children with asthma was widely neglected to date. The aim of this study is to understand the microbiome, the microbial immunology, and the proteome of exacerbated children and adolescents with wheeze and asthma. Considering that a certain proportion of wheezers may show a progression to asthma, the comparison of both groups provides important information regarding clinical and phenotype stratification. Thus, deep nasopharyngeal swab specimens, nasal epithelial spheroid (NAEsp) cultures, and blood samples of acute exacerbated wheezers (WH), asthmatics (AB), and healthy controls (HC) were used for culture (n = 146), 16 S-rRNA gene amplicon sequencing (n = 64), and proteomic and cytokine analyses. Interestingly, Proteobacteria were over-represented in WH, whereas Firmicutes and Bacteroidetes were associated with AB. In contrast, Actinobacteria commonly colonized HCs. Moreover, Staphylococcaceae, Enterobacteriaceae, Burkholderiaceae, Xanthobacteraceae, and Sphingomonadaceae were significantly more abundant in AB compared to WH and HC. The α-diversity analyses demonstrated an increase of bacterial abundance levels in atopic AB and a decrease in WH samples. Microbiome profiles of atopic WH differed significantly from atopic AB, whereby atopic samples of WH were more homogeneous than those of non-atopic subjects. The NAEsp bacterial exposure experiments provided a disrupted epithelial cell integrity, a cytokine release, and cohort-specific proteomic differences especially for Moraxella catarrhalis cultures. This comprehensive dataset contributes to a deeper insight into the poorly understood plasticity of the nasal microbiota, and, in particular, may enforce our understanding in the pathogenesis of asthma exacerbation in childhood.